Effects of accute cafeinne administration on problem solving in rats (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
In problem situations, animals emit new behaviors that emerge according to their training history. In this study, the influence of acute caffeine administration on problem solving in rats was investigated. The problem-solving situation used were climb and dig, developed by Neves Filho et al. (2015). The procedure involved: (1) discriminative training, (2) open field, (3) pre-test, (4) training of the prerequisite dig and climbing repertoires, (5) recovery training, (6) test, and (7) open field (reexposure). Animals were divided into two groups: acute administration and control group (without caffeine). No animal solved the problem in the pre-test. No rat under the effect of caffeine solved the problem in the test phase, after the training of pre-requisite repertoires. Only animals from the control group, three of four, solved the problem in the test phase. The data indicate that caffeine intake interfered with the emergence of the solution response. Caffeine modulated problem solving in the acute group probably making it more difficult for animals to discriminate and functionally generalized the relationships between stimuli learned in Phase 4.
Keywords: Coffe; Interconnection of Behavioral Repertoires; Problem Solving; Creativity; Pharmacology; Animal Models